1990
DOI: 10.1016/0014-5793(90)80723-v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heparin on proliferation and signalling in BC3H‐1 muscle cells

Abstract: We studied binding and growth inhibitory properties of different glycosaminoglycans in growing and differentiated BC3H-I muscle cells. Heparin (10 pg/ml) and heparan sulfate (10 ,ug/ml) significantly inhibited DNA synthesis in growing and differentiated cells, as monitored by PH]thymidine incorporation. Binding of heparin to BC3H-1 cells was specific and time-dependent. Heparan sulfate was the only glycosaminoglycan able to displace PH]heparin (I&,, 3.2 x lo-' M), although it was lo-fold less effective than he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…However, low molecular weight heparins differ from high molecular weight heparin in their binding to proteins (Lane, 1989): they have lower affinity for proteins such as fibronectin (Dawes & Pavuk, 1991) or Platelet factor 4 and histidine-rich glycoprotein (Lane et al, 1986). Moreover, they have much lower affinity for the heparin-binding sites on endothelial cells (Vannucchi et al, 1988) and BC3H-l muscle cells (Vannucchi et al, 1990b). In this paper we show that confluent cultures of Balb/c 3T3 cells bear high affinity binding sites for heparin with Kd values of the same magnitude as the IC50 shown in the antiproliferative experiments.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…However, low molecular weight heparins differ from high molecular weight heparin in their binding to proteins (Lane, 1989): they have lower affinity for proteins such as fibronectin (Dawes & Pavuk, 1991) or Platelet factor 4 and histidine-rich glycoprotein (Lane et al, 1986). Moreover, they have much lower affinity for the heparin-binding sites on endothelial cells (Vannucchi et al, 1988) and BC3H-l muscle cells (Vannucchi et al, 1990b). In this paper we show that confluent cultures of Balb/c 3T3 cells bear high affinity binding sites for heparin with Kd values of the same magnitude as the IC50 shown in the antiproliferative experiments.…”
Section: Discussionsupporting
confidence: 52%
“…We have previously demonstrated that heparin inhibited seruminduced phosphoinositide turnover in BC3H-1 muscle cells and the interference with serum growth factors was proposed as a possible mechanism (Vannucchi et al, 1990b). PDGF accounts for approximately 50% of the platelet derived mitogenic activity of serum; the remaining activity appears to be due to other growth factors (Ross et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…It could be intracellular, extracellular, or both. Heparin is taken into cells, such as fibroblasts, 18 by a process of cell-surface binding 19,20 followed by internalization and metabolism of the glycosaminoglycan into oligosaccharides. 21,22 Internalized heparin or its metabolites could change cellular metabolism, 23 resulting in an alteration in the production of extracellular matrix proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Specific heparin-binding sites have been shown to occur in a smooth muscle cell type (BC3H-1), and binding is considered a preliminary to cellular internalization (46). Possible intracellular sites for heparin action are inhibition of IP 3 -dependent intracellular calcium mobilization after phospholipase C activation (47), which may affect calcium-dependent phospholipase A 2 secondarily.…”
Section: Discussionmentioning
confidence: 99%